2014
DOI: 10.1016/j.aorn.2013.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Applications for Radio‐frequency Identification Technology in the Perioperative Setting

Abstract: We implemented a two-year project to develop a security-gated management system for the perioperative setting using radio-frequency identification (RFID) technology to enhance the management efficiency of the OR. We installed RFID readers beside the entrances to the OR and changing areas to receive and process signals from the RFID tags that we sewed into surgical scrub attire and shoes. The system also required integrating automatic access control panels, computerized lockers, light-emitting diode (LED) infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In the context of economic adjustments and resource optimization in global healthcare without jeopardizing patient safety, reliable systems to monitor the consumption of materials through ensuring their full traceability are needed [13, 28]. The RFID automation of logistic systems represents a significant step forward in patient-focused models for consignment and high value product management [4].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of economic adjustments and resource optimization in global healthcare without jeopardizing patient safety, reliable systems to monitor the consumption of materials through ensuring their full traceability are needed [13, 28]. The RFID automation of logistic systems represents a significant step forward in patient-focused models for consignment and high value product management [4].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al 1 suggested tracking personnel, keys, and attire as three important elements relative to use of technology in the OR. In our study, participants ranked the use of Personnel RTLS 15th of the 17 items and ranked it lowest for WFE and QPC.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to control personnel flow in the OR has important implications for perioperative settings. Zhao et al 1 implemented a two‐year project using an RFID system to facilitate workflow management through the OR. The purpose of the project was to control the flow of OR personnel, reduce OR costs, and improve the management and efficiency of processes such as registration and scrub clothing changes.…”
Section: Statement Of Purposesmentioning
confidence: 99%
See 1 more Smart Citation
“…The system analysed how the number of door openings during surgical procedures increase the number of particles in the air, increasing the risks of wound contamination. Similarly, Zhao et al [58] assessed the quality of the surgical procedures by monitoring the usage of personal protective equipment and hand disinfection practices by surgical teams in operating rooms by using radiofrequency sensors.…”
Section: Clinical-related Aspectsmentioning
confidence: 99%